The Effect Of Parking Retribution Receipts On The Original Revenue Of Palopo City - Shinta Muhariati; Andika Rusli; Andi Dahri Adi Patra (LP2M IAIN Palopo, 2025)
This research discusses the influence of the parking levy revenues on Palopo City's original regional income with the aim of finding out the effect of parking on Palopo City's original regional income (PAD). Using primary data taken was then processed using SPSS 26 using a simple regression analysis method because it only has variables including parking fees and local revenue, the results of the research show that there is a significant influence between the parking fee on original income area of Palopo City through SPPS 26 testing using a simple regression analysis method because it only has 2 variables including parking fees and local original income. The results of the hypothesis test proved that there was a significant influence between the parking levy variable and the local revenue variable in Palopo City.